Empowering Cattle Keepers for On-Farm Production and Utilization of Green Fodder and Planting Materials: Hybrid (HB) Napier (Pennisetum Purpureum) in Sitapur District of Uttar Pradesh - Shantanu Kumar Dubey, U.S. Gautam, Atar Singh, Anand Singh and Anand Singh (Indian Journal of Extension Education, 2018)
An action oriented field study was conducted among 30 rural youths of five villages in Biswan block ofSitapur district in Uttar Pradesh. The selected rural youths were facilitated for utilizing Hybrid (HB) Napiergrasses for production of green fodder and rooted slips during rainy and winter seasons. The on-farm assessmenttrials were conducted across five villages among the selected youth with twofold objectives to see the utilizationof Hybrid Napier grasses for green fodder purpose as well as enabling them for rooted slips production. Theresearch variables included seasonal adaptability of the rooted slips, differential seasonal performance, technoeconomicfeasibility of utilizing the HB Napier for green fodder and rooted slips production and potentialwindows for better utilization of the rooted slips produced on-farm. Results showed better adaptability ofrooted slips HB Napier in winter (60 days) as compared to rainyseason (30 days). However, on all othertechnical parameters and yield of rainy season (900-1000 q/ha/year) harvest out rated the winter season(600-700 q/yr/ha). The B:C ratio for rooted slips production was found 3.1 compared to 6.31 for green fodderproduction using HB Napiers.The necessary institutional arrangements and stakeholders’ partnership for outscaling this promising technology has been discussed.